Assessment of local muscle deformations using multi-modal imaging and finite element modeling - Pamuk, Uluç. (Thesis (Ph.D.)-Bogazici University. Institute of Biomedical Engineering, 2019., 2019)
In vivo assessment of muscle deformations, including inﬂuence of non-muscular tissues such as NVTs, aponeuroses, fasciæ or overlying skin, is key due to functional relevance of tissue connectivity within limb. In integral framework of anatomy, understanding deformations in muscle and non-muscular connectome, and mechanical interactions therein, is crucial. Muscle deformations caused by external loads, e.g., KT, are conceivable and crucial to quantify when exploring KT’s unknown action mechanism. Continuity of muscle ﬁbers and extra-cellular matrix (ECM) is also of relevance. Titin was so far considered as passive spring of sarcomere, a view now changing due to its altered properties in active state. Yet, muscle ﬁber–ECM interaction can further change titin’s inﬂuence. This thesis aims to address these by MRI image registration, DTI and FEM. MRI analyses of KT showed principal tissue strains deviated from KT loading direction. By DTI tractography and MRI analyses combined, muscle ﬁber and shear strains upon passive knee extension were determined. Strains were non-uniform along fascicles, which lengthened (8.7%) and shortened (7.5%), overall. Passive muscle FEM indicated role of NVT connectivity in imposing myofascial loads that cause strain non-uniformities. FEM with active titin showed increased total stress, with little increase from cross-bridges and much from titin. Depending on titin formulation, strain non-uniformities varied, yet persisted. Active force increased or leveled beyond optimum length. Strains were shorter overall: a shorter sarcomere eﬀect. In sum, new non-invasive in vivo DTI and MRI methods are used to assess muscle tissue deformations; FEM allowed proposing new views incorporating epimuscular interactions within limb, with implications for muscle pathophysiology.|Keywords : Diﬀusion Tensor Imaging (DTI); Magnetic Resonance Imaging (MRI); Myofascial loads; Kinesio Taping (KT); Muscle ﬁber direction strains; Principal tissue strains; Neuro-vascular Tracts (NVT); Finite Element Modeling (FEM)
Keywords: Muscles -- Diseases.; Magnetic resonance imaging.